COVID-19 pandemic impacts to Dentistry - MEDEIROS,Matheus Simões (2020)
ABSTRACT Objective: To achieve a literature review on the impacts of COVID-19 on dentistry. Methods: Analysis of scientific articles contained in the LILACS and PubMed platforms that fulfill the informative purpose of the research. Results: The production of aerosols during dental procedures could be highlighted as the most dangerous agent, the literature recommends restricting the type of service only to emergencies and reducing the use of rotating instruments or cough-inducing equipaments. New protective measures must be taken, such as the type of PPE used and the frequency of asepsis of the workplace, since any surface that has been exposed to oral or pharyngeal secretions may contain a load of viral particles, an online triage is also recommended before any assistance. Due to the easy spreading of this disease and the possibility of asymptomatic patients, the current best measure is avoiding the execution of procediments. Conclusion: COVID-19 will be a milestone for the current generations of health professionals, it could also be an advance for use distance technologies and integration of new biosafety techniques.